Missi di Era Disrupsi dan Pandemic - Markus Suwandi; Sayang Tarigan (Formosa Journal of Multidisciplinary Research, 2022)
Jesus the Messiah, the Son of God was in His divine mission has prophesied His presence since the fall of the first man from sin. The person of Jesus has always been an interestings discussion and continued until the postmodern era when there was disruption and pandemics. Jesus Christ gave the disciples a missionary mandate to preach the Gospel. Observe the basics mission mandated by Jesus in John 20:21-22. But how is the Christian mission in the era of disruption and pandemics? This paper uses a descriptive methode approach with literature studies and exposition of reference texts as the database. God revealed His love in the mission of sending His Son into the world with a holy purpose to atone for sins. Likewise, Jesus sent disciples in every era encountered to preach the gospel. The Trinity divines God synergizes with the mission of the disciples. From this discussion, it is unequivocal that mission has a biblical basis in every era that existings.